Perspectives of Open-Air Processing to Enable Perovskite Solar Cell Manufacturing - Rolston, Nicholas; Sleugh, Andrew; Chen, Justin P.; Zhao, Oliver; Colburn, Thomas W.; Flick, Austin C.; Dauskardt, Reinhold H. (Frontiers in Energy Research, 2021)
We report high throughput open-air processing techniques for the scalable production of all device and barrier layers for perovskite photovoltaics (PV). This work discusses and resolves some of the most formidable barriers to module-level scaling that the perovskite community has been facing. Our advanced technoeconomic manufacturing analysis indicates that vacuum-based processes with high capital expenditures (CapEx) and low throughputs dominate the cost of production. Open-air fabrication methods offer low CapEx routes to manufacturing, but achieving reproducibility in ambient conditions with varying relative humidity has been a persistent challenge. The use of rapid processing methods with plasma curing to convert films from the solution-state enables reproducibility, moisture immunity, and the highest perovskite PV efficiency produced in open-air. These methods are readily translatable to in-line processing where layers are sequentially deposited without the need for lengthy post-annealing steps that reduce throughput and involve additional equipment. Significant progress is demonstrated in reduced manufacturing costs as perovskites contend as a commercially viable next-generation thin film PV technology.